Elogio del disaccordo: per una filosofia politica del linguaggio - Serra, Mauro (Rivista Italiana di Filosofia del Linguaggio, 2012)
The aim of this paper is to show, through the example of Gorgias’ Encomium of Helen, the fruitful role of disagreement in argumentative theory and practice. Gorgias’ Encomium contains a seeming contradiction, that has puzzled the scholars. While in the opening section of the text, Gorgias outlines the strong connection between truth and logos, about one third of the same text is devoted to showing that the wonderful power of logos depends not on its truth, but on its skillful use. So logos is akin to brute force that moves the listener in an almost physical way. Yet the seeming contradiction disappears, when we understand that logos is for Gorgias a competitive and agonistic practice, in which one logos can always be confuted by another (logically stronger) one. From this point of view truth and opinion are two interchangeable conditions and even Gorgias’ logos about Helen will be truthful only until it is, if possible, confuted by another one. In the final section of the paper I show that this model of language functioning can have some political consequences: argumentation as a logically competitive practice plays a leading role in developing democratic citizenship